Protein folding in vivo - Bardwell, James (Henry Stewart Talks, 2012)
Protein folding in vivo, Protein folding as facilitated by the acid inducible chaperone HdeA, Optimization of folding in vivo illustrates a tradeoff between stability and function, The Spy chaperone